Worldfulness, Role-enrichment & Moving Rituals: Design Ideas for CRPGs - Champion, Erik (DiGRA, 2016)
Roles and rituals are essential for creating, situating and maintaining cultural practices. Computer Role-Playing games (CRPGs) and virtual online worlds that appear to simulate different cultures are well known and highly popular. So it might appear that the roles and rituals of traditional cultures are easily ported to computer games. However, I contend that the meaning behind worlds, rituals and roles are not fully explored in these digital games and virtual worlds and that more needs to be done in order to create worldfulness, moving rituals and role enrichment. I will provide examples from The Elder Scrolls IV: Oblivion and The Elder Scrolls V: Skyrim (Bethesda, 2006, 2011) to reveal some of the difficulties in creating digitally simulated social and cultural worlds, but I will also suggest some design ideas that could improve them in terms of cultural presence and social presence.